Comparison of different cooling methods for extending shelf life of postharvest broccoli - Tian, Ding; Fen, Liu; Jiangang, Ling; Mengli, Kang; Jingfen, Yu; Xingqian, Ye; Donghong, Liu (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: This study aimed to investigate and compare the effects of vacuum cooling, cooling water and cold room methods on the shelf life of broccoli. The experiments were divided into four groups: vacuum cooling (A), ice-water cooling (B), cold room cooling (C) and control. The cooling rate and changes of weight loss, respiratory rate, chlorophyll, vitamin C, reducing sugar content and sensory properties were measured at intervals of five days. The results indicated that vacuum cooling was the most effective method for extending the shelf life of postharvest broccoli in terms of cooling rate, respiration rate, chlorophyll, vitamin C, reducing sugar and sensory properties. Moreover, spraying the broccoli with water during the vacuum cooling process resulted in a significant reduction in weight compared with the other two cooling methods and did not reduce the quality of the broccoli. Consequently, vacuum cooling treatment can be applied to broccoli after harvest in the field to maintain quality during transportation and storage. Additionally, the application of water spraying during vacuum cooling can considerably reduce the negative influence caused by vacuum cooling.Keywords: vacuum cooling, broccoli, shelf life, water spraying, postharvestDOI: 10.3965/j.ijabe.20160906.2107Citation: Ding T, Liu F, Ling J G, Kang M L, Yu J F, Ye X Q, et al. Comparison of different cooling methods for extending shelf life of postharvest broccoli. Int J Agric & Biol Eng, 2016; 9(6): 178-185.